1998
DOI: 10.1093/jnci/90.18.1371
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen for Prevention of Breast Cancer: Report of the National Surgical Adjuvant Breast and Bowel Project P-1 Study

Abstract: Tamoxifen decreases the incidence of invasive and noninvasive breast cancer. Despite side effects resulting from administration of tamoxifen, its use as a breast cancer preventive agent is appropriate in many women at increased risk for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
3,056
8
83

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,960 publications
(3,240 citation statements)
references
References 51 publications
60
3,056
8
83
Order By: Relevance
“…[9][10][11][12][13][14][15] As tamoxifen has been associated with increased incidence of thromboembolic events and endometrial cancer, it is necessary to evaluate risk versus benefit for each patient. 16 …”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] As tamoxifen has been associated with increased incidence of thromboembolic events and endometrial cancer, it is necessary to evaluate risk versus benefit for each patient. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen has also been demonstrated to be of value in reducing the risk of primary invasive and pre-malignant breast cancer in high-risk women in North America (Fisher et al, 1998), and of contralateral breast cancer in unselected women (Early Breast Cancer Trialists' Collaborative Group, 1998). The large National Surgical Adjuvant Breast and Bowel Project (NSABP) breast cancer prevention trial reported a highly significant reduction in the incidence of invasive breast cancer among women randomized to tamoxifen, versus placebo (Fisher et al, 1998). In an subset analysis of the NSABP database, genetic mutation status was determined by DNA sequencing on 288 women with incident breast cancer (King et al, 2001).…”
Section: Tamoxifen and Raloxifenementioning
confidence: 99%
“…Tamoxifen administration is known to be associated with gynecological side effects such as endometrial hyperplasia, polyps and cancer [1][2][3][4]. Although most of these changes are benign, the wide range of abnormalities induced by tamoxifen has led to a number of gynecological interventions in symptomatic women to exclude malignant disease.…”
Section: Introductionmentioning
confidence: 99%